Kafâ’ah Contextualization in an Effort to Form Harmonious Family in the Modern Era: An Analysis Of Fazlur Rahman's Double Movement - Fajar, Mokhammad Samson; al Badr, Faris (Universitas Islam Negeri Raden Intan Lampung, 2020)
Kafā’ah is a marriage law that has relatively little attention from Islamic jurists. This is because kafā’ah is less adaptable to changes in people's lives. Because kafā’ah is identical with the Arab cultural heritage before Islam. But factually this kafā’ah is still a legacy in the books of the fuqaha'. This research is focused on revealing the relevance of the concept of the kafā’ah of the fuqaha' with the changing times of the modern era. As well as how to contextualize the concept of kafā’ah in this modern era so that it truly becomes a path to family harmony. In uncovering the problem, the double movement theory or Fadzlurrahman dual interpretation is used, in which this interpretation becomes the knife of analysis by revealing how the current condition of the kafā’ah is then drawn to the kafā’ah of the past and how the response of the Qur'an and the Sunnah. Then the moral values of the Qur'an and the Sunnah are taken using reasoning ratios so that conclusions can be drawn in accordance with current needs. The conclusion of this research is that the concept of kafā’ah in the book of fiqh is not relevant to the needs of this modern era, where kafā’ah in the modern era is more interpreted in terms of equality and ability (competence) to get married, which is different from the kafā’ah of the past which is more nuanced feudalistic.